Tel Shechem/Tell Balatah: the rampart of wall A and the character of the Middle Bronze IIC compound - Usishḳin, Daṿid (Israel exploration journal, 2019)
This paper discusses the Middle Bronze IIC compound at Tel Shechem/Tell Balatah. First, it discusses Wall A (the Cyclopean Wall) and presents new data supporting the view that it was a core-wall incorporated in the earthen fills of the compound and not a massive fortification wall. Second, it discusses the character of the compound, arguing that it was an unfortified, sacred compound centred on the Tower Temple.